Viral BS : medical myths and why we fall for them - Yasmin, Seema, 1982- (Johns Hopkins University Press, 2021)
"This book dissects medical myths and pseudoscience and explores how misinformation can spread faster than microbes. Yasmin debunks public health myths ranging from the spurious link between vaccines and autism to the truth about so-called chemtrails left behind by airplanes. In short chapters covering popular myths, Yasmin parses the science behind fearful rumors and models how to be a more informed consumer of health news"--